2016
DOI: 10.1016/j.msec.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Development of PLGA-coated β-TCP scaffolds containing VEGF for bone tissue engineering

Abstract: Bone tissue engineering is sought to apply strategies for bone defects healing without limitations and short-comings of using either bone autografts or allografts and xenografts. The aim of this study was to fabricate a thin layer poly(lactic-co-glycolic) acid (PLGA) coated beta-tricalcium phosphate (β-TCP) scaffold with sustained release of vascular endothelial growth factor (VEGF). PLGA coating increased compressive strength of the β-TCP scaffolds significantly. For in vitro evaluations, canine mesenchymal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(48 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…High levels of ALP is normally expressed at the end of cell proliferation and during the maturation period [75, 76]. VEGF expression lead to an upregulation of BMP-2 and plays an important role in bone growth and repair in addition to its main role of vascularization [19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of ALP is normally expressed at the end of cell proliferation and during the maturation period [75, 76]. VEGF expression lead to an upregulation of BMP-2 and plays an important role in bone growth and repair in addition to its main role of vascularization [19]. …”
Section: Discussionmentioning
confidence: 99%
“…These systems not only protect the encapsulated molecule against aggressive environments but also release the molecule in a sustainable manner. Poly (lactic-co-glycolic acid) (PLGA) has been widely used for growth factor sustained delivery in different forms including coating layers and microspheres [3841]. Growth factor loaded PLGA microspheres can be easily incorporated into the ink to be 3D printed.…”
Section: Introductionmentioning
confidence: 99%
“…270 Therefore, bone tissue engineering has attracted considerable attention from researchers as a promising strategy for repairing bone defects without the limitations and shortcomings of using either bone autografts, allografts, or xenografts. 271 …”
Section: Injectable Hydrogels For Bone Tissue Engineeringmentioning
confidence: 99%
“…It was found that the scaffold with sustained-and/or localized-release of VEGF could be favorable for bone regeneration in vitro. 35 …”
Section: Structural Properties Of Biodegradable Polymersmentioning
confidence: 99%